Esperanto for histones: CENP-A, not CenH3, is the centromeric histone H3 variant - Earnshaw, William C.; Erhardt, Sylvia; Cleveland, D. W. (Chromosome research, 2013)
The first centromeric protein identified in any species was CENP-A, a divergent member of the histone H3 family that was recognised by autoantibodies from patients with scleroderma-spectrum disease. It has recently been suggested to rename this protein CenH3. Here, we argue that the original name should be maintained both because it is the basis of a long established nomenclature for centromere proteins and because it avoids confusion due to the presence of canonical histone H3 at centromeres.